Security and quality issues in IT projects - El Desouki, Hassan; Armstrong, Helen (Centre for Security, Communications & Network Research, 2010)
The need for the inclusion of security and quality requirements early in the life of IT projects has been recognised for more than three decades. But have we learned from past experience? This paper presents four recent case studies of IT projects that have gone wrong for a variety of security and quality reasons. The problem is not a simple one to solve, however, valuable lessons can be learned from past experience. This paper relates to a project that is still a work-in-progress.